Antígenos leucocitários humanos (HLA) na avaliação imunológica para a seleção de receptor-doador para transplantes - Raquel Aparecida Fabreti de Oliveira (2014)
The Human leukocyte antigens (HLA) are highly polymorphic and influence in the transplantation success of organs and tissues. The distribution of alleles and haplotypes HLA vary in the world population, making it difficult the identification of unrelated individuals genetically similar in HLA. The objective was to study the HLA molecule in the context of transplantation, including the identification of new allelic variants of HLA, analyze the genetic diversity of the population in order to determine possible differences among regions of Brazil, and elaborate a protocol to classify organ recipients by risk for rejection and thereby improve kidney transplantation survival. The sample was composed by from two distinct groups. In the group one, 566 healthy unrelated individuals registered as donors in REDOME (Brazilian Registry of Bone Marrow Donors Volunteer), In this study, the HLA data were analyzed using several methods and algorithms, some of which were developed during this thesis work. The sequences of the new HLA-A*80:03, HLA-B*07:184, -B*27:102, -B*41:27, -B*42:19, -B*42:20, - B*50:32, -B*51:151, -B*57:63, -B*57:64, -B*58:42 de classe I e HLA-DRB1*04:11:03, - DRB1*10:05, -DRB1*15:94, -DRB1*16:22 were deposited in EMBL, GenBank and DDBJ database. In the Brazilian population, was observed a heterogeneous genetic composition, with different distributions in HLA allelic and haplotype frequencies among Brazilian regions. It may contribute to development of strategies for search voluntary bone marrow donors for REDOME and also assist in developing clinical protocols to optimize the assessment of compatibility between recipient-donor. The group two was composed by 337 recipients who underwent kidney transplantation from living or deceased donors. The receptors were classified as low risk (LR), medium (MR), high (HR) or very high risk (SR) having rejection based on PRA Single Antigen Beads (SAB) test. The survival of the grafts was assessed after one year of transplantation. In general, in the clinical study of transplant patients, it was observed that patients classified as low risk group had fewer episodes of rejection and better graft survival when compared with patients in the group of medium, high and very high risk (p-value<0.05).